Application of MRI Imaging of Focal Adenomyosis and Adenomyotic Cyst: A Case Report of a 42-Year-Old Female - JMP, Guarín; JV, Río; GM, Benítez; FD, Cordón (Achievements and Challenges of Medicine and Medical Science Vol. 2, 2024)
Adenomyosis is a common benign uterine disease characterized by the presence of ectopic endometrial glands and stroma within the myometrium. This happens when the normal boundary between the endometrial basal layer and the myometrium is disrupted. Adenomyosis is defined by the presence of ectopic endometrial glands and stroma within the myometrium. This happens when the normal boundary between the endometrial basal layer and the myometrium is disrupted. It is hypothesized that factors such as uterine trauma, pregnancy, postpartum endometritis, or caesarean delivery may contribute to its development. Adenomyosis has been noted to occur in about 30% of the general female population and the reported prevalence of adenomyosis in hysterectomy specimens varies from 5% to 70%. A case of a 42-year-old female, nulligravida, with a medical history of complete spontaneous miscarriage five years ago, was reported. The patient experienced uncontrolled bleeding, necessitating treatment with cervical cerclage. The patient presented with menstrual menometrorrhagia and dysmenorrhea treated with oral contraceptive pills but the symptoms persisted. Transvaginal sonography showed a globular uterine enlargement with one leiomyoma and thickened uterine walls. Vascular malformation or adenomyosis were suspected. An MRI was performed, confirming findings consistent with adenomyosis. Adenomyosis can become a debilitating disease in women. It was also noted that the definitive treatment of adenomyosis is currently hysterectomy; however, uterine artery embolization has been described as an alternative treatment, though its outcomes are not always satisfactory. MRI offers the advantage of radiation-free imaging, superior visualization of uterine morphology, and the ability to identify specific signs that facilitate accurate diagnosis.